Immuno-histochemical features of chronic gastro-duodenitis in children with connective tissue dysplasia - O. M. Mukvich; T. D. Zadorozhnaja; O. V. Lavrenchuk; T. N. Archakova; S. M. Kylyhevych (Patologìâ)
Aim of the work: Better predicting the outcome of chronic gastro-duodenitis (CGD) and plan therapeutic intervention in children with connective tissue dysplasia (CTD) requires the accurate account of the pathological processes associated with CTD. Evaluations of histochemical and immune-histochemical changes in the small intestinal (SI) and stomach mucosa, particularly changes in collagen IV expression, improve the diagnostics of chronic CGD and predicting the disease outcome, providing a rationale for therapy approaches.